Dampak Bokashi Kotoran Ternak dalam Pengurangan Pemakaian Pupuk Anorganik pada Budidaya Tanaman Tomat - Darwin Habinsaran Pangaribuan; Muhammad Yasir; Novisha Kurnia Utami (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
The objective of this research was to study the effect of bokashi livestock on the growth and yield of tomatoes. The experiment was conducted in Bandar Lampung from October 2009 until February 2010. The experimental design was randomized complete block design with 3 replications. The treatments were: control; inorganic fertilizers at a recommended rate of (kg ha-1) 135 N, 75 P2O5, and 110 K2O (RR); chicken manure bokashi + RR; chicken manure bokashi + 50% RR; cow manure bokashi + RR; cow manure bokashi + 50% RR; sheep manure bokashi + RR; sheep manure bokashi + 50% RR; horse manure bokashi + RR; horse manure bokashi + 50% RR. Each bokashi treatment was applied at the rate of 20 ton ha-1. The result of experiment showed that chicken manure bokashi was the best among bokashi livestock. The application of 50% RR combined with chicken, cow, sheep or horse manure bokashi gave a higher yield than treatment with inorganic fertilizer at recommended rates. These results demostrated that the application of bokashi livestock could potentially reduce the use of inorganic fertilizers while maintaining higher yield. Keywords: animal manure, inorganic fertilizer, bokashi livestock, tomatoes